The effect of incorporating hydroxyapatite into Type II glass ionomer cement on flexural strength and the examination of fractured surfaces using scanning electron microscopy - Rahmitasari, Fitria; Cevanti, Twi Agnita; Prabowo, Puguh Bayu; Sularsih, Sularsih; Prananingrum, Widyasri (Odonto : Dental Journal, 2023)
Background: Glass ionomer cement (GIC) is widely recognized as the prevailing direct esthetic restorative material. In order for a restoration material to be considered effective, possess favorable physical and mechanical properties. Incorporating with hydroxyapatite (HA) can provide these properties. This research is to investigate the impact of integrating HA into GIC on the flexural strength and scanning electron microscopy (SEM) of the fractured surfaces. Methods: The study consisted of 28 samples of GIC, which are fabricated in the shape of rectangular prisms (25x2x2mm). The samples were divided into four groups n=7. Group 1 is a control group (GIC), Group 2 GIC+2%HA, group 3 GIC+2%HA, and GIC+4%HA. The flexural strength of the sample was evaluated by a Universal testing machine, followed by an examination of the fracture surface using SEM. Result: The Brown-Forsythe was used as data analysis to examine the flexural strength values across all groups, resulting in a statistically significant p-value of less than 0.05. The addition of HA does not result in a significant increase in the flexural strength value of the glass ionomer cement (GIC). The integration of microstructure based on scanning electron microscopy (SEM) pictures demonstrates improved visual quality following the incorporation of HA. Conclusion: The addition of HA to GIC did not result in a significant change in flexural strength compared to the control group. However, GIC group with 2% HA exhibited the highest average flexural strength value among all the groups